Equine Herpesvirus-I Infection in Horses: Recent Updates on its Pathogenicity, Vaccination, and Preventive Management Strategies. - Rivas Caceres, Raymundo Rene (2020)
Equine herpesvirus-1 (EHV-1) is one of the most common and ubiquitous viral pathogens infecting equines, particularly horses worldwide. The EHV-1 is known to induce not only humoral but also cellular immune responses in horses. Respiratory distress, abortion in pregnant mares, neurological disorders, and neonatal foal deaths represent EHV-1 infection. Despite the limited success of inactivated, subunit, live, and DNA vaccines, over the past few decades, vaccination remains the prime preventive option to combat EHV-1 infection in horses. However, current vaccines lack the potentiality to protect the neurological form of infections in horses. There is desperate necessity to search effectual EHV-1 vaccines that may stimulate not only mucosal and systemic cellular immunity but also humoral immunity in the horses. This review highlights the state of knowledge regarding EHV-1 biology, EHV-1 pathogenesis, and disparate vaccines studied in the past to prevent EHV-1 infection. The review also underlines the best management strategies which certainly need to be adopted by veterinarians in order to avoid and prevent EHV-1 infection and outbreak in horses in the future.